1990
DOI: 10.2307/1243040
|View full text |Cite
|
Sign up to set email alerts
|

Grain Price Expectations of Illinois Farmers and Grain Merchandisers

Abstract: The study's purpose is to measure the extent to which futures and option prices reflect the subjective price distribution of a subset of market participants, farmers, and grain merchandisers in Illinois. Findings suggest that in most instances the futures price is an appropriate proxy for expected price. However, volatilities implied by option premia usually overestimate the subjective variances of producers and merchandisers. These differences between individual and market expectations of variance are consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
10

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 13 publications
1
14
0
10
Order By: Relevance
“…This is, amongst others, supported by the analysis of Musser et al (1996). Furthermore, Eales et al (1990) find that the prices for futures and options grain contracts reflect the price expectations of Illinois farmers and grain merchandisers. Consequently, farmers with price expectations below the actual price level are expected to be more willing to use PHI.…”
Section: Hypothesis Generationsupporting
confidence: 53%
“…This is, amongst others, supported by the analysis of Musser et al (1996). Furthermore, Eales et al (1990) find that the prices for futures and options grain contracts reflect the price expectations of Illinois farmers and grain merchandisers. Consequently, farmers with price expectations below the actual price level are expected to be more willing to use PHI.…”
Section: Hypothesis Generationsupporting
confidence: 53%
“…9 Another study found this to be true despite learning and accumulated evidence. 10 Studies providing evidence for the overconfidence effect within economic contexts in particular include Ganguly et al (2000) and Barber and Odean (2001), who provide evidence for an overconfidence effect in asset market evaluations and stock trading, Madsen (1994) who finds overconfidence effects in manufacturing data, Camerer and Lovallo (1999) who provide experimental evidence that overconfidence leads to excessive entry decisions in the marketplace, Eales et al (1990) who find that overconfidence biases Illinois farmers and grain merchandisers evaluations of option prices, and Golec and Tamarkin (1995) who find evidence for the overconfidence effect influencing betting behavior. While the purpose of this paper is to test for evidence of confirmatory bias, not its subsequent manifestation of overconfidence, these studies all point to the economic relevance of this issue for behavioral decision making.…”
Section: Literature and Methodological Reviewmentioning
confidence: 99%
“…Either way, such data manipulation leads to biased estimates (both in support of the a priori hypothesis) and poor decision-making behavior. 3 Overconfidence, a behavioral phenomenon related to confirmatory bias, has been subject to some scrutiny in the economics literature (see, for example, Ganguly et al 2000;Madsen 1994;Camerer 1997;Camerer and Lovallo 1999;Eales et al 1990;Dubra 2004;Hvide 2002;Golec and Tamarkin 1995;Barber and Odean 2001), but similar attention has not been paid to the confirmatory bias effect itself. 4 While it appears that direct tests of the confirmatory bias phenomenon have yet to be published in the economics literature, it is possible to reevaluate previously published work in light of the confirmatory bias effect.…”
Section: Introductionmentioning
confidence: 99%
“…Three strategies, all involving selling a futures contract together with an options position, are appropriate if the producer expects price mean to be the same as or lower than the futures price. Eales et al (1990) found that corn and soybean producers tend to agree with the market's price mean expectations, although the producers' expectations of price volatility tend to be lower than the market. Given these types of expectations, the futures hedge alone or in combination with a single options position may be practical (near-optimal) in many hedging situations.…”
Section: Discussionmentioning
confidence: 91%